Displacement of the Facial Nerve by Deep Parotid Lobe Lesions in the Pediatric Population. Issue 5 (19th August 2019) - Maddalozzo, John; Johnston, Douglas R.; Isaac, Andre; Bhushan, Bharat; Rastatter, Jeffrey C.
Abstract : Objectives: To describe and investigate facial nerve displacement in deep lobe parotid lesions in children and to determine clinical and radiographic predictors of abnormal facial nerve position. Methods: Retrospective case review of children who underwent total parotidectomy for deep lobe parotid lesions at a tertiary care center between January 2014 and December 2017. Aberrant facial nerve trajectory was defined as ascension of the nerve at an angle of 45° or greater. Elongation was defined as the main trunk >2 cm in length. Patient demographics, radiographic, pathologic results, postoperative nerve weakness, and intraoperative nerve findings were collected. Wilcoxon rank‐sum test and Fisher's exact test were used to assess the associations between variables of interest and facial nerve position. Results: A total of 20 patients were included. The mean age was 7.7 ± 5 years. The most common pathologies were lymphatic malformation, pleomorphic adenoma, and first branchial cleft cyst. Twelve out of twenty (60.0%) patients had abnormal intraoperative facial nerve position. There was no significant difference in distribution of pathologies between those with or without an abnormal intraoperative nerve position ( P = .41). Neither radiographic lesion size nor distance between the lesion and proximal portion of the facial nerve (mastoid tip) were associated with abnormal facial nerve position intraoperatively. Conclusion: Pediatric deep lobe parotid lesions can displace the facial nerve and distort its anatomy in a posterior lateral direction, in approximately 60% of patients. Statistical analysis of increased numbers of patients to further define predictors of aberrant nerve course is warranted. Level of Evidence: 4.